PENGARUH MOTIVASI DAN PENGETAHUAN TENTANG AKAD TERHADAP MINAT ASATIDZ MENABUNG DI BANK SYARIAH (STUDI KASUS PONDOK PESANTREN UMMUL MASAKIN DESA KAMPUNG PULAU KECAMATAN MUARA BULIAN) - Azkiya, Mujahid Royhan Azkiya; Azkiya, Mujahid Royhan; Sissah, Sissah; Ridho, M. Taufik (MARGIN: Journal of Islamic Banking, 2024)
Sharia banks have been in Indonesia for a long time and continue to experience development in various circles of society. Sharia banking provides opportunities to grow among Islamic boarding schools in Indonesia. Usually we are familiar with Islamic boarding schools that have Islamic nuances, but in this research it was found that the Islamic boarding schools in Ummul Masakin still have Asatidz who still use conventional banks. The aim of this research is to determine the influence of motivation and knowledge about contracts on interest in savings at Sharia banks. This type of research uses quantitative methods. The population in this study was 100 respondents. In this study, a saturated sampling technique was used, namely taking the population based on the number of Asatidz in the Ummul Masakin Islamic boarding school. The data analysis technique used to answer all problem formulations uses multiple linear regression analysis using the SPSS version 29 program. The results of the t test show that the motivation variable has a tcount value of 1.798 > ttable 1.717, so H1 is accepted, the knowledge variable has a tcount value of 5.398 > ttable is 1.660, then H2 is accepted and the R2 test is 0.579, this means that the interest in saving variable can be explained by the motivation and knowledge variables. The t test results of the variable that is very influential in interest in saving, namely the knowledge variable, has a t value of 5.398.